Effects Of Soft/Quiet Running Cues Versus Changing to a Forefoot Strike Pattern on Gait Mechanics - Lucas Sarantos; David J. Zeppetelli; Cole A. Dempsey; Lauren K. Sara; Caleb D. Johnson (Medicine & Science in Sports & Exercise, 2026)
Purpose: To compare changes in running biomechanics between two gait modifications: cues to run softly and quietly (SOF) and shifting to a forefoot strike pattern (FFS). Methods: Thirty-eight individuals completed testing, including running with habitual gait (HAB) and the two gait modifications, while biomechanical data were collected. Variables of interest included joint angles and moments, knee stiffness, and ground reaction forces. Repeated measures analysis of variance was used to compare gait conditions. Results: The SOF condition showed higher peak knee flexion angles and excursion, foot strike angles (vs. HAB and FFS), and higher peak and initial contact ankle dorsiflexion angles, peak eversion angles, and lower initial contact ankle inversion angles (vs. FFS). The FFS condition resulted in a more plantarflexed and inverted ankle at initial contact, as well as a more plantarflexed foot. The SOF condition resulted in reduced peaks and loading rates for vertical and posterior forces, however FFS led to reduced vertical loading rates compared to HAB and SOF. For joint moments, the SOF condition showed increased hip flexion and extension moments and reduced knee stiffness (vs. HAB and FFS), and reduced ankle plantarflexion moments (vs. FFS). The FFS condition also showed increased knee flexion and ankle plantarflexion moments compared to HAB. Conclusions: The SOF modification was shown to be a viable alternative to FFS for reducing several key aspects of biomechanical loading during running, including sagittal knee and ankle moments and knee stiffness, as well as peaks and loading rates for vertical and posterior ground reaction forces. However, the increases in hip joint moments should lead to some caution and warrant further investigation.